PENGGUNAAN GEOGEBRA DALAM PENGEMBANGAN PEMBELAJARAN INTERAKTIF MATA PELAJARAN MATEMATIKA SMA - Hedi; Sri Nur Yuliyawati (Politeknik Negeri Sriwijaya, 2023)
Mathematics learning is often complained of by most high school teachers because it is not able to attract students' interest. This can be overcome by applying mathematical software so that it has a positive impact and increases student interest in learning. For this reason, Community Service Activities are carried out in the form of